# How to solve 3 1/4 = 1/2 + x with answer?

Welcome to my article 3 1/4 = 1/2+x. This question is taken from the simplification lesson.

The solution of this question has been explained in a very simple way by a well-known teacher by doing addition, subtraction, and fractions.

For complete information on how to solve this question 3 1/4 = 1/2+x, read and understand it carefully till the end.

Let us know how to solve this question 3 1/4 = 1/2+x.

First write the question on the page of the notebook

## 3 1/4 = 1/2 + x

We see that mixed fractions are available in the given question. First of all convert this mixed fraction into a simple fraction.

\displaystyle 3\frac{1}{4}=\frac{1}{2}+x \displaystyle \frac{{4\text{x}3+1}}{4}=\frac{1}{2}+x \displaystyle \frac{{12+1}}{4}=\frac{1}{2}+x \displaystyle \frac{{13}}{4}=\frac{1}{2}+xreverse the numbers

\displaystyle \frac{{13}}{4}-\frac{1}{2}=xWe are seeing that each of these posts are different.

So we solve by finding the least common factor of their denominator.

Hence the exact solution of this question is **11/4**.

## See citation of other similar quadratic equation

**example number 1**

## 2x^-11x+15=0

\displaystyle 2{{x}^{2}}-11x+15=0To solve such a problem, the formulas of the quadratic equation \displaystyle a{{x}^{2}}+bx+c=0 compare.

Comparing a=2 , b=-11, c=15

since we know that

D=(b ^2 -4ac )

Where D = Distributed

Now substituting the values of terms in D=(b ^2 -4ac )

[(-11)^2 -4x2x15 ]

121-120

1

Then ,

Let the original be \displaystyle \alpha and\beta then \displaystyle \alpha =\frac{{-b=\sqrt{D}}}{{2a}} The formula for \displaystyle \alpha makes sense.

\displaystyle \alpha =\frac{{11+1}}{{2\text{x}2}} \displaystyle \frac{{12}}{4} \displaystyle =3Similarly, extracting the value of \displaystyle \beta gives \displaystyle \beta =\frac{5}{2} .

So the answer to this question is 3 and 5/2

How to solve 3 1/4 = 1/2 + x with answer? This article has been completely solved by tireless effort from our side, still if any error remains in it then definitely write us your opinion in the comment box. If you like or understand the methods of solving all the questions in this article, then send it to your friends who are in need.

Note: If you have any such question, then definitely send it by writing in our comment box to get the answer.

Your question will be answered from our side.

Thank you once again from our side for reading or understanding this article completely.

## Example no 2

\displaystyle \frac{{{{{(3)}}^{{n+4}}}-{{{(6\text{x}3)}}^{{n+1}}}}}{{{{{(3)}}^{{n+2}}}}}Solve this question as follows

\displaystyle \frac{{{{{(3)}}^{{n+4}}}-{{{(2\text{x}2\text{x}3)}}^{{n+1}}}}}{{{{{(3)}}^{{n+2}}}}} \displaystyle \frac{{{{{(3)}}^{{n+4}}}-{{{(2\text{x}{{\text{3}}^{2}})}}^{{n+1}}}}}{{{{{(3)}}^{{n+2}}}}} \displaystyle \frac{{{{{(3)}}^{{n+4}}}-{{{(2\text{x3})}}^{{n+1}}}}}{{{{{(3)}}^{{n+2}}}}}In this \displaystyle {{{{(\text{3})}}^{{n+1}}}} if required.

\displaystyle \frac{{{{{(3)}}^{{n+4}}}-[{{3}^{2}}\text{2 }!!]!!\text{ }}}{{{{{(3)}}^{{n+2}}}}}\displaystyle {{{{(3)}}^{{n+2}}}} Delete when down and up.

\displaystyle \begin{array}{l}{{3}^{2}}-2\3\text{x}3-2\9-2\7Answer\end{array}